Genetic study with autosomal STR markers in people of the Peruvian jungle for human identification purposes. Issue 3 (26th July 2021) - Neyra Rivera, Carlos David; Delgado Ramos, Edgardo; Díaz Soria, Fabiola; Quispe Ramírez, José Santos; Ge, Jianye; Budowle, Bruce
Abstract: In the present study allele frequencies and other population parameters were determined for forensically-relevant Short Tandem Repeat (STR) markers in 278 Peruvians born and resident in the Peruvian jungle in total and separated into the subpopulations Amazonas, Loreto, and Madre de Dios. The samples were analyzed using the VeriFiler TM Express kit which enables typing of 23 STR loci and an amelogenin marker for sex determination. The parameters assessed and reported herein were allele frequencies, the power of discrimination (PD), departures from Hardy-Weinberg equilibrium, and estimates of the population distances. Under the assumption of independence, when comparing the population of the Peruvian jungle with a Peruvian mestizo population, Aymara population of Peru, Ashaninca of Peru, Hispanic Americans, and a Bolivia mestizo population, the largest genetic distance (Fst) was with the Hispanic population (Fst = 0.0343), and the smallest was with the Peruvian mestizo population (Fst = 0.0126). The jungle subpopulation showed greater distances in some comparisons. This study provides population data from a unique population residing in the Peruvian jungle which could be used to estimate various statistics of forensic interest for human identification.